Transforming Mission Theology. (January 2020) - Whiteman, Darrell
Charles Van Engen's book Transforming Mission Theology is reviewed, highlighting the integration of biblical, theological, contextual, and personal domains in the development of mission theology. The book is noteworthy for its balance of diverse perspectives, its depth of insight, its awareness of the impact of globalization on the local church, and its balance of ecumenical and evangelical perspectives.